O-010 Microbial Metabolites Establish a Gradient of Protons, Which Mediate Interkingdom Host-Microbiome Cross-Talk and Maintain Intestinal Homeostasis via Two Proton-Sensing GPRs. (February 2017) - Alam, Ashfaqul; Wu, Huixia; Matthews, Jason; Saeedi, Bejan; Jones, Rheinallt; Neish, Andrew
Abstract : Background: The mammalian intestine houses a complex microbial community, which fundamentally influences the development and activation of the immune system, and is integral to the repair of damaged intestinal mucosa. Intestinal damage is observed in inflammatory bowel disease (IBD), enteric infections, as well as following surgical trauma, and environmental insults. Tissue restitution is a complex but coordinated cellular process to repair gut mucosa, which involves both cellular proliferation and migration. We recently reported that the intestinal wound microenvironment specifically enriches a mucosa-associated microbial consortia, which enhanced epithelial wound healing. The mammalian microbiota generates a diverse array of microbial metabolites. We hypothesize that the intestinal microbiome-produced metabolites generate a gradient of protons, which influence intestinal barrier function and mucosal homeostasis. Methods: For this purpose, we performed a preliminary analysis by HPLC-qTOF mass spectrometry-based global metabolomic profiling of germ-free and conventional mice. Results: We found an elevated synthesis of acidic microbial metabolites, which established an extracellular pH gradient with more acidic pH at the apex of the colonic crypt in conventional mice, but not in germfree animals. We found that the colonic epithelial cells of conventional mice express increased levels of proton-sensing GPRs (GPR4 and GPR68). Intriguingly, the murine colonic content or its specific metabolite 2-hydroxy-4-methylpentanoic acid (HMP) decreases the extracellular pH to modulate claudin-4 dependent paracellular permeability and regulate the proliferation of colonic epithelial cells in a GPR68 and GPR4-dependent manner. Interestingly, we found that GPR68 and GPR4 are activated by different levels of acidic pH, show differential expression pattern along the colonic crypt, and also have an opposing functional role in colonic epithelial cell proliferation. Conclusions: Collectively, our findings suggest that the reciprocal functions of GPR4 and GPR68 as the sensor of microbially produced protons are potentially involved in maintenance of gut mucosal homeostasis and barrier function.